Current advances on RIPK2 and its inhibitors in pathological processes: a comprehensive review - Shen, Shanshan; Lu, Chen; Ling, Tao; Zheng, Yanan (Frontiers in Molecular Neuroscience, 2025)
Receptor-Interacting Protein Kinase 2 (RIPK2) is a critical component of the signaling pathways downstream of Nucleotide-binding oligomerization domain-like receptor (NOD-like receptor), playing a vital role in the immune response, particularly in the context of cellular transport, adaptive immunity, and tumorigenesis. Recent advances have further clarified the complex roles of RIPK2, offering insights into its structural and functional characteristics. In this review, we provide a comprehensive overview of RIPK2’s involvement in signaling, examine the development of RIPK2 inhibitors, and discuss novel strategies for targeting RIPK2 in therapeutic applications. Additionally, we highlight the dynamic interactions between RIPK2 and NOD-like receptors and explore future directions for improving RIPK2-targeted therapies.